PEMBELAJARAN FISIKA DENGAN PENDEKATAN KETERAMPILAN PROSES MELALUI METODE DEMONSTRASI MENGGUNAKAN MEDIA RIIL DAN MEDIA VIRTUIL DITINJAU DARI MOTIVASI DAN GAYA BERFIKIR SISWA - Kurnianto, Ary Wahyu (Universitas Hamzanwadi, 2011)
The purposes of this study are to know: (1) the effect of learning media toward students achievement; (2) the effect high and low motivation toward students achievement; (3) the effect of concrete and abstract thinking styles toward students achievement; (4) the interaction between the learning media and motivation toward students achievement; (5) the interaction between the learning media and thinking styles toward students achievement; (6) the interaction between motivation and thinking styles towards students achievement; (7) the interaction among learning media, motivation and thinking styles toward students achievement. The research used experimental method, was conducted from January to May 2010. Population was all students at grade VII SMP 2 Girisubo academic year 2009/2010 that consisted of four classes. Sample was taken using cluster random sampling technique and consisted of two classes. The fist class was treated using virtual demonstration and second class was treated real demonstration. The data was collected using test for students achievement, and questioner for students motivation and thinking style, and observation sheet for students affective achievements. The research hypotheses was tested using ANOVA with 2x2x2 factorial design and calculated with software minitab 15. From data analysis can be concluded that: (1) there is no effects of learning media toward students cognitive (p value = 0.618) and affective (p value = 0.822) achievement, (2) there is an effect students high motivation towards cognitive (p value = 0.000) and affective (p value = 0.008) achievement, (3) there is no effect of concrete and abstract thinking styles toward students cognitive (p value = 0.233) and affective (p value = 0.233) achievement, (4) There is no interactions between the learning media and students motivation toward (p value = 0.365) but there is interaction between the learning media and the motivation toward affective ( p value = 0.037) achievement, (5) there is no interaction between the learning media and students thinking styles toward cognitive (p value = 0.112) and affective (p value = 0.256) achievement, (6) there is interaction between motivation and students thinking style toward cognitive (p value = 0.042) but there is no interaction between motivation and students thinking styles on affective (p value = 0.780) achievement, (7) There are no interactions among learning media motivation and thinking styles of the students toward cognitive learning (p value = 0.977) and affective (p value = 0.089) achievement.